Menegakkan Demokrasi dan Konstitusionalitas Pemilihan Umum Kepala Daerah - Sri Hastuti Puspitasari (Jurnal Konstitusi, 2011)
The Constitutional Court was not born only to maintain and uphold the Constitution, the Constitutional Court will continue to defend democracy was thus born. Because of the elections is now entered the realm of the general election regime, constitutionally, the authority of the Constitutional Court to resolve election disputes are the results in the paragraph of article 24C sub section (1) the 1945 Constitution of the State of the Republic of Indonesia. Only then the legitimacy of the formal authority of the Constitutional Court explicitly mentioned in the general election dispute referred to in article 236C of the law number 12 year 2008, concerning the amandment of law number 32 of 2004. In the settlement of the election dispute General, the Court not is based only on the results of the calculation of quantitative of the number of votes have been counted, but the Court made a breakthrough that the calculations which, if it is that there is a difference in the calculation of the noise exposure of the door to manipulation that is structural systematic and massive, then the role of democratization and the Court to defend the constitutionality of the general election that is an essential step to bring into the substantive  justice